THE EFFECT OF MOTOR GAMES IN IMPROVING MOTOR RESPONSE SPEED AND BLOCKING SKILL FOR VOLLEYBALL PLAYERS - Sabah Jameel, Dr. Omar (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2024)
The research aims to prepare movement games and identify the extent of their effect in improving the speed of movement response and blocking. The researcher used the experimental method in a single-group design with two pre- and post-tests for a sample of (10) players from the Heat Sports Club in volleyball for ages (10-13) years. Pre-tests were conducted and then motor games were applied. They included (24) educational training units at a pace of three units each week spread over eight weeks. Motor games were used in the main section, with a duration of (40) minutes, and then the researcher used Appropriate statistical methods in order to reach results. The most important conclusion was that motor games have a positive effect in improving the speed of motor response and blocking.